2017
DOI: 10.1128/aem.02680-16
|View full text |Cite
|
Sign up to set email alerts
|

Season-Specific Occurrence of Potentially Pathogenic Vibrio spp. on the Southern Coast of South Korea

Abstract: Vibrio species are widely distributed in warm estuarine and coastal environments, and they can infect humans through the consumption of raw and mishandled contaminated seafood. In this study, we aimed to isolate and observe the distribution of enteropathogenic Vibrio spp. from environments of the southern coast of South Korea over a season cycle. A total of 10,983 isolates of Vibrio spp. were obtained from tidal water and mud samples over a 1-year period from five sampling sites along the southwest coast of So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
5
28
3
1
Order By: Relevance
“…2%). The obtained results of seasonal prevalence of V. alginolyticus were higher than what reported by Di et al (2017) who isolated V. alginolyticus at a prevalence of 8.57% in summer, 5.30% in autumn, 2.04% in spring and 0.81% in winter. This was in a disagreement with (Wang et al, 2017) who reported that V. alginolyticus were not associated with a particular season.…”
Section: Discussioncontrasting
confidence: 80%
“…2%). The obtained results of seasonal prevalence of V. alginolyticus were higher than what reported by Di et al (2017) who isolated V. alginolyticus at a prevalence of 8.57% in summer, 5.30% in autumn, 2.04% in spring and 0.81% in winter. This was in a disagreement with (Wang et al, 2017) who reported that V. alginolyticus were not associated with a particular season.…”
Section: Discussioncontrasting
confidence: 80%
“…Therefore, the detection rate of V. vulnificus varies from 6% to 69% in different seasons, globally [ 40 , 41 , 42 ]. In this study, the detection rate of V. vulnificus in the river basins was higher in the winter season (20.8%) than in the summer season (12.5%), which is unique and different from what was shown in most of the previous studies [ 41 , 43 ]. The river site of our investigation is located in the subtropical area, where the weather temperature at the sampling time was over 33 °C in summer and approximately 22 °C in winter; thus, the winter season in Taiwan is more suitable for the survival of V. vulnificus , where, as previously highlighted, the optimal growth temperature ranges from 20–30 °C [ 9 , 43 , 44 , 45 , 46 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Therefore, fishery products from the West Sea may become cross-contaminated from these environments. In particular, Di et al (2017) detected V. cholerae (0.1%) in the tidal water collected from the southern coast in June and V. cholerae (0.5%) in the tidal water in September 2013. Therefore, the microbial contamination of products from the West Sea should be monitored.…”
Section: Introductionmentioning
confidence: 93%